Marginal and internal fit of zirconia copings obtained using different digital scanning methods - Lorena Oliveira PEDROCHE; Sérgio Rocha BERNARDES; Moira Pedroso LEÃO; Cibele Cândida de Almeida KINTOPP; Gisele Maria CORRER; Bárbara Pick ORNAGHI; Carla Castiglia GONZAGA
Abstract The objective of this study was to evaluate the marginal and internal fit of zirconia copings obtained with different digital scanning methods. A human mandibular first molar was set in a typodont with its adjacent and antagonist teeth and prepared for an all-ceramic crown. Digital impressions were made using an intraoral scanner (3Shape). Polyvinyl siloxane impressions and Type IV gypsum models were also obtained and scanned with a benchtop laboratory scanner (3Shape D700). Ten zirconia copings were fabricated for each group using CAD-CAM technology. The marginal and internal fit of the zirconia copings was assessed by the silicone replica technique. Four sections of each replica were obtained, and each section was evaluated at four points: marginal gap (MG), axial wall (AW), axio-occlusal edge (AO) and centro-occlusal wall (CO), using an image analyzing software. The data were submitted to one-way ANOVA and Tukey's test (α = 0.05). They showed statistically significant differences for MG, AO and CO. Regarding MG, intraoral scanning showed lower gap values, whereas gypsum model scanning showed higher gap values. Regarding AO and CO, intraoral digital scanning showed lower gap values. Polyvinyl siloxane impression scanning and gypsum model scanning showed higher gap values and were statistically similar. It can be concluded that intraoral digital scanning provided a lower mean gap value, in comparison with conventional impressions and gypsum casts scanned with a standard benchtop laboratory scanner.